Gas turbine plant MB6001 maintenance in Lеbanon - Хуссейн, Эль Хожайри (Proceedings of National Aviation University (archive), 2004)
Failure statistics and main performance data of gas turbine plant MB6001 operating in Lebanon are given in the article. The gas turbine plant operating conditions have been investigated. Causes of failure were analyzed, it was revealed that corrosion and follow-up damages of third turbine stage blades are main failures.